Perbandingan Tingkat Kelelahan Dan Kemampuan Activity Daily Living Pre Hemodialisa Dengan Post Hemodialisa Pada Pasien Gagal Ginjal Kronik Di Indonesia Kidney Care Club - Erina Rusmiati (2020)
Patients with chronic kidney failure who have reached stage five must undergo hemodialysis therapy. Hemodialysis therapy in the long run will cause patients to feel various side effects, such as fatigue and disruption of their daily activities. This study aims to determine the difference of the level of fatigue and the ability of ADL between patients with pre hemodialysis chronic renal failure and post hemodialysis chronic renal failure in IKCC. This research is a comparative descriptive study with a cross-sectional approach. The sampling technique of this research was purposive sampling. The number of samples were 67 respondents. The results of the study are based on the Wilcoxon Sign test, the level of pre fatigue with post hemodialysis (p value = 0,000<0,05), and the ability of ADL pre with post hemodialysis (p value = 0,024<0,05). It was concluded that there was a difference of the level of fatigue and the ability of ADL pre hemodialysis with post hemodialysis in patients with chronic kidney failure in the IKCC. Then from the results of this study, it is expected that respondents focus on the condition of their bodies so that they can control fatigue and seek help in completing daily activities and the kidney community in Indonesia can develop information related to the side effects of hemodialysis therapy such as fatigue and disruption of daily activities. Keywords : Chronic Kidney Failure, Hemodialysis, Fatigue, Activity Daily Living